(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The doctrine of res judicata plays a crucial role in ensuring legal certainty, procedural efficiency, and the finality of dispute resolution. While firmly embedded in national judicial systems, its application in international arbitration remains complex due to the absence of a uniform codified framework. This article examines the operation of res judicata in international arbitration, focusing on its conceptual foundations, practical challenges, and comparative dimensions. The analysis explores the dual manifestations of res judicata in arbitration—claim preclusion and issue preclusion—and highlights the difficulties arising from divergent national standards, the role of the lex arbitri, and the recognition and enforceability requirements under the New York Convention. Particular attention is given to the absence of explicit regulation of res judicata in major international instruments, including the UNCITRAL Model Law on International Commercial Arbitration, and to the resulting reliance on choice-of-law approaches and general principles of law by arbitral tribunals. By examining comparative perspectives from the procedural laws of Uzbekistan and Italy, the article demonstrates that res judicata is consistently grounded in the triple identity test and extends to matters that were or could have been raised in prior proceedings.